A carbohydrate ingestion intervention in an elite athlete who follows a low-carbohydrate high-fat diet - Webster, C. C.; Swart, J.; Noakes, T. D.; Smith, J. A. (International Journal of Sports Physiology and Performance, 2018)
This case study documents the performance of an elite-level, exceptionally well-fat-adapted endurance athlete as he reintroduced carbohydrate (CHO) ingestion during high-intensity training. He had followed a strict low-CHO high-fat (LCHF) diet for 2 y, during which he ate approximately 80 g of CHO per day and trained and raced while ingesting only water. While following this diet, he earned numerous podium finishes in triathlons of various distances. However, he approached the authors to test whether CHO supplementation during exercise would further increase his high-intensity performance without affecting his fat adaptation. This 7-wk n=1 investigation included a 4-wk habitual LCHF diet phase during which he drank only water during training and performance trials and a 3-wk habitual diet plus CHO ingestion phase (LCHF+CHO) during which he followed his usual LCHF diet but ingested 60 g/h CHO during 8 high-intensity training sessions and performance trials. After each phase, rates of fat oxidation and 30-s sprint, 4-min sprint, 20-km time trial (TT), and 100-km TT performances were measured. Compared with LCHF, 20-km TT time improved by 2.8% after LCHF?+?CHO, which would be a large difference in competition. There was no change in 30-s sprint power, a small improvement in 4-min sprint power (1.6%), and a small reduction in 100-km TT time (1.1%). The authors conclude that CHO ingestion during exercise was likely beneficial for this fat-adapted athlete during high-intensity endurance-type exercise (4-30 min) but likely did not benefit his short-sprint or prolonged endurance performance.